Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Inap di RSUD Panembahan Senopati Bantul - Fathoni, Muhammad Isnaini; Herlambang, Susatyo (Jurnal Bisnis, Manajemen, dan Akuntansi, 2024)
This study aims to determine the effect of service quality on inpatient satisfaction at Panembahan Senopati Hospital, Bantul. The population is people, while the sample used is 83 inpatients who perform inpatient services. The sampling technique in this study was accidental sampling, data collection was carried out by taking a questionnaire with a Likert scale. The analytical method used in this study was simple regression analysis with the SPSS 22 application. The results of the study (t test) showed that service quality had a significant effect on patient satisfaction with a significant value of 0.000 <0.05. The test results for the coefficient of determination obtained R Square of 0.302. this shows that the dependent variable of customer satisfaction is 30.2% influenced by the independent variable service quality, while 69.8% is influenced by other variables that have not been examined in this study.